2019
DOI: 10.3390/inorganics7110128
|View full text |Cite
|
Sign up to set email alerts
|

99mTc Labelling Strategies for the Development of Potential Nitroimidazolic Hypoxia Imaging Agents

Abstract: Technetium-99m has a rich coordination chemistry that offers many possibilities in terms of oxidation states and donor atom sets. Modifications in the structure of the technetium complexes could be very useful for fine tuning the physicochemical and biological properties of potential 99m Tc radiopharmaceuticals. However, systematic study of the influence of the labelling strategy on the "in vitro" and "in vivo" behaviour is necessary for a rational design of radiopharmaceuticals. Herein we present a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…When compared with flutamide, which has a high PPB (95 ± 1%), all the complexes presented clearly lower values. These results show the impact of the donor atoms set on the overall physicochemical behavior of Tc-labeled small biomolecules, a fact that has been corroborated by our group and other research groups before [ 14 , 15 , 17 ]. A comparison of C3 , which has the lowest PPB, with C4 , which has the highest value, also demonstrates that the length of the linker has, as expected, a considerable impact on the physicochemical properties of the labeled compounds.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When compared with flutamide, which has a high PPB (95 ± 1%), all the complexes presented clearly lower values. These results show the impact of the donor atoms set on the overall physicochemical behavior of Tc-labeled small biomolecules, a fact that has been corroborated by our group and other research groups before [ 14 , 15 , 17 ]. A comparison of C3 , which has the lowest PPB, with C4 , which has the highest value, also demonstrates that the length of the linker has, as expected, a considerable impact on the physicochemical properties of the labeled compounds.…”
Section: Resultssupporting
confidence: 88%
“…Even if these early attempts to prepare 99m Tc-labeled derivatives were not successful, further research should be undertaken since the influences of the chelator and spacer in the biological properties of potential radiopharmaceuticals are well documented in the literature for a variety of molecular targets [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…99m Tc has been the most widely used SPECT isotope due to its in-house availability and reasonable cost, and it possesses ideal nuclide properties (t 1/2 = 6 h, E g =140 keV), as well as rich coordination chemistry with various oxidation states and donor atom sets. 20 In 2020, Lindner et al reported several 99m Tc-labeled FAPI radiotracers, 21 and 99m Tc-FAPI-34 with high affinity and significant tumor uptake was applied for preclinical models and SPECT of patients with metastasized ovarian and pancreatic cancer. In addition, the therapeutic use of 188 Re of this agent is attractive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nitroimidazole is the most widely used pharmacophore for hypoxia imaging because it can differentiate hypoxic and normoxic tissue. The potential for targeting hypoxia mostly depends on the single-electron reduction potential (SERP); the more positive the SERP value of a nitroimidazole is, the better its reduction potential of enzymes in aerobic cells [ 25 ]. Therefore, 2-nitroimidazole with the highest SERP value has become the most popular pharmacophore for the development of hypoxia probes compared with 4-nitroimidazole and 5-nitroimidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Technetium-99m has been the most widely used SPECT isotope because it possesses ideal nuclide properties ( t 1/2 = 6 h, Eg = 140 keV) and rich coordination chemistry with various oxidation states and donor atom sets [ 25 ]. In addition, its in-house availability and reasonable cost have resulted in wide clinical use, especially in many developing countries and less-developed regions [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%